2022
DOI: 10.1111/all.15494
|View full text |Cite
|
Sign up to set email alerts
|

Unique and common TCR repertoire features of Ni2+‐, Co2+‐, and Pd2+‐specific human CD154 + CD4+ T cells

Abstract: Background: Apart from Ni 2+ , Co 2+ , and Pd 2+ ions commonly trigger T cell-mediated allergic contact dermatitis. However, in vitro frequencies of metal-specific T cells and the mechanisms of antigen recognition remain unclear.Methods: Here, we utilized a CD154 upregulation assay to quantify Ni 2+ -, Co 2+ -, and Pd 2+ -specific CD4+ T cells in peripheral blood mononuclear cells (PBMC). Involved αβ T cell receptor (TCR) repertoires were analyzed by high-throughput sequencing.Results: Peripheral blood mononuc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 95 publications
(254 reference statements)
0
4
0
Order By: Relevance
“…Using the novel activation‐induced marker assay, our previous research has shown that T cell activation is highly concentration‐dependent, peaking at about 400 μM for all three metal ions 3 . Notably, at this concentration, Pd 2+ activates a large fraction of the T cell pool.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…Using the novel activation‐induced marker assay, our previous research has shown that T cell activation is highly concentration‐dependent, peaking at about 400 μM for all three metal ions 3 . Notably, at this concentration, Pd 2+ activates a large fraction of the T cell pool.…”
Section: Discussionmentioning
confidence: 97%
“…Of the three metals analysed, Pd 2+ had the lowest concentration in the remaining skin, regardless of whether PTPs or a metal salt solution were applied. This suggests that even though Pd 2+ has the ability to activate a large portion of the T cell pool, only a very small fraction of Pd 2+ ‐specific T cells become engaged at the low Pd 2+ concentrations in the skin 3 . This may explain why palladium allergies are less common than nickel allergies, in addition to a generally lower dermal exposure.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations